Influence of Microwave Irradiation on Extraction of Chitosan from Shrimp Shell Waste - Dwi Titik Apriyanti; Heru Susanto; Nur Rokhati (Reaktor, 2018)
Chitosan is natural polysaccharides which is nontoxic, biodegradable, and biocompatible and have many advantages in various kinds of fields including health, food, agriculture, and industry. Chitosan usually take long time to extract by conventional method for deacetylation process of chitin. Raw material for chitosan can be found in shrimp shell waste. Chitosan manufactures usually need high temperatures and chemicals in large quantities and it takes much time and consumes a lot of energy where will give bad effect to the environment. Recently microwave irradiation as nonconventional energy sources is widely used in chemical reactions. To reduce the impact of environmental pollution due to excessive use of chemical treatment, the objective of this work is processing chitosan under microwave irradiation. Expected production of chitosan with the same mass requires fewer chemicals than conventional heating. In particular, the study will examine the effect of making the chitosan and adding chemicals, reaction time and operating temperature and degree of deacetylation in chitosan with conventional heating methods that the results will be compared using a microwave. In this research will be developed to the design and fabrication of prototype scale extractor for manufacturing chitosan from shrimp shell waste after optimum results obtained from the research laboratory scale. From the research we can conclude that microwave will speed up reaction time. FTIR also showed functional group of chitosan formed from microwave irradiation have same results.  Keywords: chitosan, shrimp shells, microwave